Antecedent conditions determine the biogeochemical response of coastal soils to seawater exposure. (February 2021) - Sengupta, Aditi; Stegen, James C.; Bond-Lamberty, Ben; Rivas-Ubach, Albert; Zheng, Jianqiu; Handakumbura, Pubudu P.; Norris, Cooper; Peterson, Matthew J.; Yabusaki, Steven B.; Bailey, Vanessa L.; Ward, Nicholas D.
Abstract: Coastal landscapes are increasingly exposed to seawater due to sea level rise and extreme weather events. The biogeochemical responses of these vulnerable ecosystems are poorly understood, limiting our ability to predict how their role in local and global biogeochemical cycles will shift under future conditions. Here we evaluate how antecedent conditions influence the biogeochemical response of soil to seawater inundation events based on a 42-day laboratory incubation experiment with soils collected from a natural salinity gradient across a coastal floodplain. We quantified influences of seawater inundation on intact soil cores through high-frequency carbon dioxide (CO2 ) and methane (CH4 ) gas fluxes measurements as well as ultrahigh resolution characterization of organic matter chemistry and metabolites. Mean CO2 and CH4 fluxes were higher after inundation compared to control cores for soils that had low in situ electrical conductivity (EC). Soils with low in situ EC also exhibited significant shifts in organic matter profiles after inundation, with surficial soils (0–7.5 cm) becoming more enriched in phenolic compounds, compared to deeper soils (7.5–15 cm). The number of biochemical transformations inferred from mass spectrometry increased significantly after inundation for soils with low in situ EC. Our results suggest that seawater inundation of low-salinity terrestrial environments can lead to increased microbial activity and increasing likelihood of soil carbon release, with sites experiencing infrequent or new seawater exposure likely to be more sensitive to saltwater exposure relative to sites with more frequent exposure. We conclude that the biogeochemical impacts of future seawater exposure will be modulated by antecedent conditions associated with landscape position within coastal watersheds. Graphical abstract: Image 1 Highlights: Impact of tidal inundations on coastal soils is inadequately addressed. Biogeochemical response of coastal soils to seawater inundation was investigated. CH4 and CO2 fluxes, and soil organic matter molecular features were evaluated. Low in situ electrical conductivity soils were impacted by inundation episodes. Antecedent conditions drive biogeochemical response of soils to seawater inundation.